Electron holography on HfO2/HfO2−x bilayer structures with multilevel resistive switching properties. (2nd May 2017) - Niu, G; Schubert, M A; Sharath, S U; Zaumseil, P; Vogel, S; Wenger, C; Hildebrandt, E; Bhupathi, S; Perez, E; Alff, L; Lehmann, M; Schroeder, T; et al.
Abstract: Unveiling the physical nature of the oxygen-deficient conductive filaments (CFs) that are responsible for the resistive switching of the HfO2 -based resistive random access memory (RRAM) devices represents a challenging task due to the oxygen vacancy related defect nature and nanometer size of the CFs. As a first important step to this goal, we demonstrate in this work direct visualization and a study of physico–chemical properties of oxygen-deficient amorphous HfO2− x by carrying out transmission electron microscopy electron holography as well as energy dispersive x-ray spectroscopy on HfO2 /HfO2− x bilayer heterostructures, which are realized by reactive molecular beam epitaxy. Furthermore, compared to single layer devices, Pt/HfO2 /HfO2− x /TiN bilayer devices show enhanced resistive switching characteristics with multilevel behavior, indicating their potential as electronic synapses in future neuromorphic computing applications.